A cross-sectional e-survey to map clinical practice of electrocardiogram use as a screening tool in outpatient department: India office electrocardiogram e-survey - Prajapati, Divyanshu; Prajapati, Hiren; Joshi, Vijay; Patel, Ronak; Patel, Khushbu; Mishra, Ashish; Shah, Nehal; Bhavsar, Marmik (International Journal of Advances in Medicine, 2022)
Background: Early detection of electrocardiogram (ECG) abnormalities in high risk cardiovascular patients with routine ECG screening is the need of the hour. The aim of the e-survey was to understand the use of ECG in high risk cardio-metabolically deranged patients at outpatient departments (OPDs) by Indian physicians. Methods: A cross-sectional India office ECG (IOECG) e-survey was conducted using Google form questionnaire from November 2021 to December 2021 among Indian physicians. Survey results were collected and analysed using Google form survey tool. Results: We received total of 1863 responses. The results of the survey showed that while 90% of physicians agreed to the necessity of doing 12 lead ECG of cardio-metabolically deranged patients, only 61% of all physicians could perform ECG screening in less than 40% of high risk cardio-metabolic patients mainly, due to several practical challenges. Among physicians, 40.2% physicians believed that 12 lead ECG was too time consuming, 35.8% physicians believed that the unavailability of ECG device was common reason while 27.5% physicians believed that there was a lack of trained staff. Majority of physicians (69.7%) agreed to use point of care ECG device which can be a solution for more screening of such patients whether symptomatic or asymptomatic. According to the survey, 88.7% physicians would appreciate if a portable handheld ECG device was made available to facilitate screening in their practice. Conclusions: There is a need of the portable handheld ECG device which helps physicians to screen large number of cardio-metabolically deranged patients in their busy OPDs.